Record of foraging of ants (Hymenoptera, Formicidae) in vertebrate carcasses - Maciel, Tatiane Tagliatti; Barbosa, Bruno Corrêa; Santos-Prezoto, Helba Helena; Prezoto, Fábio (Acta Scientiarum. Biological Sciences, 2016)
Knowing the importance of participation by insects at cadaverous decomposition processes, and the limited use of the family Formicidae in criminal investigations, this study aims to record the foraging activity of four genera of ants in carcasses of birds and mammals. Observations occurred accidentally in two locations in the State of Minas Gerais, Brazil. In total, seven species of ants foraging in eight vertebrate carcasses were recorded. In addition, the study reported for the first time the presence of Wasmannia in carcasses in Brazil.